Descriptive on The Factors of Myopia on Medical Students of Muslim University of Indonesia - Kurniawan, Mohammad Ali; Kusumawardhani, Sri Irmandha; Novriansyah, Zulfikri Khalil; Amir, Suliati P.; Namirah, Hanna Aulia (Jurnal Biologi Tropis, 2024)
Myopia is the most common refractive error found in the world. Myopia or nearsightedness is a refractive error that has a high prevalence in the world, especially in East Asia and Southeast Asia, with a prevalence of 80-90% in teenagers. Various studies have found factors related to the occurrence of myopia, such as genetic factors and environmental factors, such as near-work activities and its duration, lack of outdoor activities, and use of devices with digital screens. The aim of the research is to determine the relationship between these risk factors and the incidence of myopia in class of 2021 medical students of Muslim University Of Indonesia. The type of research used is analytical observational with a cross sectional study design. The sampling technique was a total sampling with 277 respondents. Data analysis method uses bivariate and multivariate analysis and is processed using chi-square statistical test and logistic regression test. There were 40 students whose myopia was confirmed or increased during learning. It was found that there was a relationship between risk factors for near-work activities and its duration and the use of devices with digital screens on the incidence of myopia with Chi Square test results of p=0.013 and p=0.045 respectively. Meanwhile, no relationship was found for other variables. The conclusion of this study is that the risk factors that most influence the incidence of myopia are near-work activities and its duration and the use of devices with digital screens.